FIGO Stage IV and Age Over 55 Years as Prognostic Predicators in Patients With Metastatic Malignant Struma Ovarii - Li, Sijian; Yang, Tengyu; Li, Xiaoyan; Zhang, Limeng; Shi, Honghui; Cheng, Ninghai; Lang, Jinghe (Frontiers in Oncology, 2020)
Introduction: Metastatic malignant struma ovarii (MSO) is an extremely rare disease that lacks treatment consensus and accurate prognosis. The objective of this study was to present the clinical, pathological, and treatment characteristics of metastatic MSO, while also investigate the overall survival (OS) rate and factors affecting prognosis in this population. Materrials and Methods: A total of 79 cases of metastatic MSO were reviewed, including 4 cases of metastatic MSO from our hospital and 75 cases selected from the literature. Logistic regression was used to identify potential factors affecting disease free survival (DFS). The Kaplan-Meier method and log-rank test were used to determine OS; further Cox regression was used to evaluate factors affecting OS. Results: The mean age of all the patients at diagnosis was 43.8 years. The most common metastatic sites were peritoneum, bone, liver, omentum and lung in descending order. Only two patients (2.6%) coexisted with local primary thyroid cancer. Follicular carcinoma (41.8%) as the most prevalent subtype, followed by papillary carcinoma, follicular variant of papillary carcinoma, and mixed follicular-papillary carcinoma. 36.7% of the patients received conservative surgery, 43.0% of them underwent aggressive surgery, and 15.2% of them did not receive any surgery. 74.7% of patients who received adjuvant therapy underwent radioiodine therapy (RAI). Logistics regression revealed that FIGO stage IV was the only prognostic factor in predicting DFS (P = 0.002; Odds Ratio [OR] 5.333; 95% confidence interval [CI]: 1.839-15.471). Only seven deaths occurred. The OS rates at 5, 10, 15 years were 89.3%, 82.4%, 65.9%, respectively. Multivariate analysis showed age over 55 years (P = 0.006; OR 9.362; 95%CI: 1.895-46.246) was the only risk factor for OS. Conclusion: Patients with metastatic MSO have an excellent disease-specific OS rate, FIGO stage IV and age over 55 years were two factors affecting disease prognosis. Conservative surgery with residual ablation by RAI should be preferred since the benefits of aggressive surgery are uncertain.